Enamel Hypoplasia and Dental Caries in Children: A Review Study - Amina Almahrog; Yousra Graf; Jbireal, J. M. (AlQalam Journal of Medical and Applied Sciences, 2025)
Abstract Enamel hypoplasia and dental caries significantly impact children’s oral health, with enamel defects increasing susceptibility to bacterial colonization and decay. This review explores the prevalence, causes, and consequences of enamel hypoplasia, particularly molar-incisor hypomineralization (MIH), emphasizing its association with systemic, genetic, and environmental factors. Dental caries remains a major public health concern, especially in low- and middle-income countries, where inadequate fluoride exposure, poor oral hygiene, and socio-economic disparities exacerbate the condition. Given the strong correlation between enamel hypoplasia and caries, early detection, preventive measures, and appropriate clinical management are essential. Public health interventions, policy development, and further research are crucial in mitigating the burden of these conditions and improving children’s oral health outcomes. Accordingly, the main aim of this review is to review recent findings on enamel hypoplasia and dental caries in children, highlighting their prevalence, causes, consequences, and the need for early detection, prevention, and public health interventions. يؤثر نقص تنسج المينا وتسوس الأسنان بشكل كبير على صحة الفم لدى الأطفال، حيث تزيد عيوب المينا من قابلية استعمار البكتيريا والتسوس. يستكشف هذا الاستعراض انتشار وأسباب وعواقب نقص تنسج المينا، وخاصة نقص تمعدن الأضراس والقواطع، مع التركيز على ارتباطه بالعوامل الجهازية والوراثية والبيئية. يظل تسوس الأسنان مصدر قلق رئيسي للصحة العامة، وخاصة في البلدان ذات الدخل المنخفض والمتوسط، حيث يؤدي التعرض غير الكافي للفلورايد، وسوء نظافة الفم، والتفاوتات الاجتماعية والاقتصادية إلى تفاقم الحالة. ونظرًا للارتباط القوي بين نقص تنسج المينا وتسوس الأسنان، فإن الاكتشاف المبكر، والتدابير الوقائية، والإدارة السريرية المناسبة ضرورية. تعد تدخلات الصحة العامة، وتطوير السياسات، والمزيد من البحث أمرًا بالغ الأهمية في تخفيف عبء هذه الحالات وتحسين نتائج صحة الفم لدى الأطفال. وعليه، فإن الهدف الرئيسي من هذه المراجعة هو مراجعة النتائج الأخيرة بشأن نقص تنسج مينا الأسنان وتسوس الأسنان لدى الأطفال، مع تسليط الضوء على انتشارها وأسبابها وعواقبها والحاجة إلى الكشف المبكر عنها والوقاية منها والتدخلات الصحية العامة